Peran Komite Keperawatan dalam Meningkatkan Mutu Pelayanan Keperawatan di Salah Satu Rumah Sakit Swasta di Yogyakarta - Titania Miranda (Universitas Ahmad Dahlan, 2021)
The Nursing Committee is a hospital apparatus that have the task to increase nursing professionalism through credential process, maintaining professional quality, professional ethics and disciplines. The committee plays a major role in increasing professionalism among the nurses, assuring the quality of nursing services in hospital. The purpose of this study is to determine the role of the Nursing Committee in improving the quality of nursing services at a private hospital in Yogyakarta. This is a qualitative research using case study approach. The participants are selected using purposive sampling technique and the data are acquired through in-depth interviews. The sub-committee of credentials has prepared the white paper, carried out the credential and recredential process. However, they lack sufficient assessors and, therefore, lack determination in timekeeping; (2) the sub-committee of professional quality has carried out nursing audits and developing sustainable profession for nurses. However, almost all committee’s member have multiple positions in the hospital. This situation has made it difficult to allocate time for program implementation; (3) the sub-committee of ethics has made ethical guidelines, disseminated the nursing ethics, created ethical reporting system, and audit ethics. However, the activities has not been regularly conducted. The nursing committee has not significantly improved the quality of nursing services as the sub-committee of credential, professional quality, and ethics has not been effective.